Psychological and somatic aspects of obesity during pregnancy - Strzałkowska, Paulina; Hobot, Maciej; Grabski, Wojciech (Quality in Sport, 2025)
Obesity in pregnancy presents a significant challenge to modern medicine due to its association with numerous adverse maternal and fetal outcomes. Pre-pregnancy obesity increases the risk of metabolic complications such as gestational diabetes, hypertension, preterm birth, and fetal macrosomia. Beyond physical health, it also negatively impacts the mental well-being of pregnant women, complicating pregnancy and postpartum recovery. This review explores the complex interplay between obesity, somatic health, and psychological factors during the reproductive period. Emphasis is placed on the necessity of interdisciplinary and holistic care models, integrating medical, nutritional, and psychological support to improve outcomes. Early preventive interventions, including lifestyle education and systematic monitoring, are essential to reduce complications. Despite growing awareness, further research is needed to develop comprehensive, individualized care strategies addressing physical, mental, and social determinants of health. Investing in such approaches is critical to enhancing maternal and offspring health, reducing healthcare burdens, and advancing clinical practice in reproductive medicine.